Myocardial Injury is More Common than Deep Venous Thrombosis after Vascular Surgery and is Associated with a High One Year Mortality Risk. (August 2018) - Górka, Jacek; Polok, Kamil; Fronczek, Jakub; Górka, Karolina; Kózka, Mateusz; Iwaszczuk, Paweł; Frołow, Marzena; Devereaux, P.J.; Biccard, Bruce; Musiał, Jacek; Szczeklik, Wojciech
Abstract : Objective/background: Venous thromboembolism (VTE) has been considered the dominant major life threatening vascular complication after non-cardiac surgery, but recent studies have shifted the emphasis toward myocardial injury after non-cardiac surgery (MINS) as a common adverse event in the peri-operative setting. The aim of the present study was to compare the incidence and influence on mortality of two dominant venous and arterial events in the peri-operative period by prospectively screening a consecutive cohort of patients undergoing vascular surgery. Methods: This was a sub-study of Vascular Events In Non-cardiac Surgery Patients Cohort Evaluation (VISION), the main objective of which was to evaluate major peri-operative complications after non-cardiac surgery. Patients undergoing vascular surgery had their blood collected to measure the Roche fifth generation high sensitivity troponin T (hsTnT) assay before and four times after surgery (6–12 h post-operatively, on the first, second, and third day following the procedure). MINS was defined as an elevated post-operative hsTnT ≥65 ng/L or an hsTnT ≥20 to <65 ng/L with an absolute change of ≥5 ng/L that was judged to be due to ischaemia. All patients underwent ultrasound venous compression testing for deep vein thrombosis (DVT) before, 4, and 7 days after surgery and follow-up was performed by telephone 30 days and 1 year after surgery. Results: In total, 164 consecutive patients were included in this sub-study. MINS was diagnosed in 39 patients (23.8%) and DVT in four patients (2.4%). The 1 year mortality was higher in MINS (9/39 [23.1%]) than non-MINS patients (9/125 [7.2%]; p  = .006). None of the patients who developed DVT died in the first year after surgery. Conclusion: MINS is a common complication after vascular surgery. It occurs more frequently than DVT and is associated with high 1 year mortality.